2019
DOI: 10.1111/pace.13754
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of hematoma with uninterrupted warfarin in patients undergoing implantation of subcutaneous implantable cardioverter defibrillator

Abstract: Background The perioperative management of anticoagulation with the use of subcutaneous implantable cardioverter‐defibrillator (S‐ICD) implantation is still evolving. Objective The purpose of this study was to assess whether it is safe to perform S‐ICD implantation with uninterrupted warfarin. Methods This is a multi‐center retrospective review of patients undergoing S‐ICD implantation between October 1, 2012 and June 30, 2017. Forty‐eight patients underwent successful S‐ICD implantation during the study perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Further, several papers have reported that an uninterrupted use of anticoagulation and antiplatelet is associated with an increased risk of hematoma. 8 , 9 , 10 Further, we believe that our ultrasound-guided methods can contribute to reducing the bleeding risk in such patients.…”
Section: Discussionmentioning
confidence: 94%
“…Further, several papers have reported that an uninterrupted use of anticoagulation and antiplatelet is associated with an increased risk of hematoma. 8 , 9 , 10 Further, we believe that our ultrasound-guided methods can contribute to reducing the bleeding risk in such patients.…”
Section: Discussionmentioning
confidence: 94%
“…implanted S‐ICD into 48 patients with 47.9% having uninterrupted warfarin therapy and 52.1% with interrupted warfarin therapy. They found an increased risk of hematoma formation in the uninterrupted group (26.1%) as oppose to the interrupted group (0.02%) 42 . More research needs to be performed on the effects of uninterrupted DOAC therapy in hematoma formation in S‐ICD insertion.…”
Section: Discussionmentioning
confidence: 98%
“…For patients on oral anticoagulant (OAC) medications, an important step to reduce the risk of infection is to establish a perioperative plan for OAC use. The use of OACs increases the risk of surgical bleeding and hematoma formation, 12,13 which is strongly associated with an increased risk of TV device‐related infections 14 . Because perioperative interruption of OACs may lead to an unacceptable risk of clotting sequelae, heparin bridging has been used as an alternative to OAC continuation during surgery, but this too is associated with an increased risk of hematoma formation 15,16 .…”
Section: Methodsmentioning
confidence: 99%